2012
DOI: 10.1055/s-0031-1298460
|View full text |Cite
|
Sign up to set email alerts
|

Orthoquinone and Naphthalenone Derivatives from Berrya ammonilla and Their Anti-Inflammatory Activity

Abstract: A new orthoquinone, berryammone A (1), and four new naphthalenone derivatives, berryammone B (2), berryammone C (3), 6-O-methylberryammone C (4), and 4-O-methylberryammone C (5), have been isolated from the stem of Berrya ammonilla, together with eleven known compounds (6-16). The structures of these new compounds were determined through spectroscopic and MS analyses. Among the isolates, compounds 1-3, 5, (+)-pinoresinol (6), and betulinic acid (12) exhibited inhibition (IC50 ≤ 4.41 µM) of superoxide anion gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…There are several publications on their effects in f MLF-treated neutrophils. For example, berryammone A and naphthalenone derivatives, berryammone B (Table 1) and 4- O -methylberryammone C, isolated from the stem of Berrya ammonilla exhibited a relatively potent inhibition of f MLF-induced O 2 −· generation and HNE release by neutrophils [116]. Likewise, a related methyl naphthalene carboxylate, lawsonaphthoate A (Table 1), and had potent inhibitory activity [73].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several publications on their effects in f MLF-treated neutrophils. For example, berryammone A and naphthalenone derivatives, berryammone B (Table 1) and 4- O -methylberryammone C, isolated from the stem of Berrya ammonilla exhibited a relatively potent inhibition of f MLF-induced O 2 −· generation and HNE release by neutrophils [116]. Likewise, a related methyl naphthalene carboxylate, lawsonaphthoate A (Table 1), and had potent inhibitory activity [73].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…Epibetulinic acid (Table 1) isolated from Pachycentria formosana demonstrated similar inhibitory effects as oleanolic acid [143], and its derivative, betulinic acid, also inhibited f MLF-induced O 2 −· production by neutrophils. However, this triterpene did not affect f MLF-induced release of HNE [116], suggesting that it has an FPR1-independent mechanism of action. Although α-amyrin, uvaol, ursolic acid, 19α-hydroxy ursolic acid, and 19α, 24-dihydroxy ursolic acid inhibited f MLF-induced O 2 −· production, all of these triterpenes also inhibited O 2 −· generation stimulated by arachidonic acid [147], suggesting nonspecific effects of these compounds and/or interaction with post-FPR1 pathways.…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…In turn, the methyl group at C-2 was evident based on HMBC correlations of this methyl group (δ H 1.52) to C-1, C-2, and C-3. Based on NMR analysis, the compound was found to be a naphthalenone derivative and a literature survey illustrated that the naphthalene analog, berryammone B, reported from the plant Berrya ammonilla, also comprises of a keto group at C-1 and a similar C-2 chiral centre as our new compound 1 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the saturated quaternary carbon at δ C 87.1 suggested that the hydroxyl group is attached to C-2. Moreover, the tentative assignment of absolute configuration of compound 1 was established by comparing specific rotation data with a similar published compound, berryammone B [ 39 ]. As a result, the chemical structure of compound 1 was confirmed to be 2-hydroxy-7-methoxy-2-methylnaphthalen-1(2 H )-one, named cichorin D based on the producing plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation